Impaired insulin signaling pathway in ovarian follicles of cows with cystic ovarian disease - Hein, Gustavo Juan (2015)
Cystic ovarian disease (COD) is an important cause of infertility in dairy cattle. Follicular cell steroidogenesis and proliferation in ovulatory follicles is stimulated by hormones such as insulin and its necessary post-receptor response. The aim of this study was to determine the expression of insulin receptor (IR), IR substrate-1 (IRS1) and phosphatidylinositol 3-kinase (PI3K), key intermediates in the insulin pathway, in control cows and cows with spontaneous COD and ACTH-induced COD. IR and IRS1 mRNA levels were greater in granulosa cells and lower in follicular cysts than in control tertiary follicles. PI3K mRNA levels were similar in all follicles evaluated, whereas the expression of IR, IRS1 and PI3K was similar in theca cells. Protein expression of IR was higher in control tertiary follicles than in the same structures in animals with COD and with cysts. IRS1 and PI3K protein expression showed the same pattern in tertiary and cystic follicles. However, the protein expression of subunit alpha p85 of PI3K was greater in theca cells from tertiary follicles than in cystic follicles. These results provide new insights into the insulin response in cows with COD. The lower gene and protein expressions of some insulin downstream effectors at an early stage of the signaling pathway could negatively influence the functionality of ovaries and contribute to follicle persistence.